I Think I Can, I Think I Can: Brand Use, Self-Efficacy, and Performance - Park, Ji Kyung; John, Deborah Roedder (Journal of Marketing Research, 2014)
When consumers struggle with a difficult task, using a brand can help them perform better. The authors report four studies showing that brand use can enhance feelings of self-efficacy, which can lead to better task performance. Students scored higher on difficult Graduate Records Examination questions when they took the test using a Massachusetts Institute of Technology pen (Study 1) and showed better athletic performance when they drank water from a Gatorade cup during strenuous athletic exercise (Studies 2 and 3). These increases in task performance were mediated by feelings of self-efficacy (Studies 3 and 4). Furthermore, the results show that not everyone experiences the beneficial effect of brand use; it depends on the person's implicit self-theory. Across studies, users adopting entity theories (“entity theorists”) showed increased self-efficacy and better task performance, whereas users adopting incremental theories (“incremental theorists”) were unaffected by brand use.